The Correlation of Self Concept and Work Ethic to Teacher’s Performance in Online Learning - Ni Putu Mita Ariska Dewi; I Wayan Wiarta (Universitas Pendidikan Ganesha, 2021)
Teachers' low work ethic can be seen from their initiative in creating creative online learning processes. This study analyzes the relationship between individual concepts and works ethic with teacher performance in online learning. In this study, the population and sample were 38 civil teachers taken by the total sampling method. Data collection uses non-test methods, namely questionnaires and document recording. The data were then analyzed using descriptive-analytic statistical techniques and inferential statistics. Based on the study results, it is known that the calculation of the correlation of individual concepts with teacher performance is 0.450702, which has a score higher than the score of the r table. It can be concluded that the hypothesis that there is a significant relationship between individual concepts and teacher performance in online learning is accepted or proven. The correlation of work ethic with teacher performance is 0.809709, which has a bigger score than the value of the r table. It can be concluded that the hypothesis that there is a significant relationship between work ethic and teacher performance in online learning is accepted or proven. An F score of 221,037 was obtained, and when compared with the F table score with df 1 = 2 and df = 35, a score of 3,267 was obtained which made the F score higher than table F. It can be concluded that the hypothesis that states there is a significant relationship between individual concepts and work ethic on teacher performance during online learning at SD Gugus VIII Mengwi 2020/2021 is accepted or proven.